Committed Dating Relationships and Mental Health Among College Students. - Whitton, Sarah W.; Weitbrecht, Eliza M.; Kuryluk, Amanda D.; Bruner, Michael R. (Journal of American College Health, 2013)
Objective: To examine whether involvement in committed dating relationships is associated with university students’ mental health (depressive symptoms and problem alcohol use, including binge drinking), and whether these associations differ by gender.Participants: A sample of 889 undergraduate students aged 18 to 25.Methods: Self-report measures of dating relationship status, depression, and problematic alcohol use were collected via an online survey from August to December 2010.Results: Involvement in a committed relationship, compared with being single, was associated with fewer depressive symptoms for college women but not for men. Committed relationship involvement was also associated with less problematic alcohol use for both genders.Conclusions: Findings suggest that involvement in committed relationships may be protective to college student mental health, and highlight the potential of healthy relationship programming to benefit student well-being.